Perception on the severity of tax evasion - Malaysian salary earning taxpayers' view / Farah Husna Mohd Fatzel - Mohd Fatzel, Farah Husna (2015)
Tax evasion is an undesirable phenomenon which cause a huge loss of government's revenue and reduces the tax system's effectiveness badly. Such a huge unpaid taxes may cause distortion in the development of the country as the revenues are needed to fund the country's facilities and infrastructures. There are tonnes of reasons as to why people evade tax. One of it is believed to be the perception, where people do not find it a severe offence and thus committing it is considered as totally acceptable. This study attempts to investigate the perception of the Malaysian salary earning taxpayers towards the severity of tax evasion. Both printed and online questionnaires were dispersed to approximately 580 random Malaysian salary earning income taxpayers One sample Mest, one-way analysis of variance and multiple regression methods were used for the data analysis. The results of the study indicate that tax evasion is perceived as an extremely severe offence. The study is expected to contribute to the tax administrative officials and regulators so they can come up with additional or amendments in regulations to enhance tax compliance. Other than that, the government may also come up with various campaigns and advertisements on the implications for failing to pay income tax which may sustain and strengthen the public's awareness on how dangerous tax evasion is. The findings may also trigger to the introduction of an additional syllabus of tax education in order to educate the students with good tax knowledge and tax morale as early as possible.